First Steps into the Microscopic Metrical Characterization of Bone Weathering in a Sample of Modern Guanaco (Lama guanicoe) from Southern Patagonia, Argentina : Implications for Patterns of Intraosseous Differential Preservation - Morales, Natalia (2017)
In many southern Patagonia archaeological bone assemblages deposited in open-air settings, a remarkable difference in preservation between shafts and epiphyses of guanaco (Lama guanicoe) long bones, leading to an overrepresentation of the latter, has been found. It has been suggested that, in dynamic sedimentary deposits like those investigated in this region, the observed pattern is mainly related to subaerial weathering or to a combination of weathering and abrasion preferentially affecting long bone shafts, processes that may have little relationship with bone mineral density (BMD). In order to investigate in more detail the relationship between weathering and bone mineral density (BMD) and cortical thickness in guanaco long bones, a microscopic (low magnification) metrical analysis of partial cross-sections from a sample of modern radii-ulnae with a various degrees of weathering was performed. Overall, the obtained results suggest that subaerial weathering can suffice to explain the observed archaeological pattern of differential intraosseous preservation, although this inference should be further supported with data from a larger sample including other long bones as well as a more complete record of the weathering sequence.